The prehistory of kláusti, klausýti, and their related forms revisited - Yamazaki, Yoko (Lietuvių kalba, 2022)
The Baltic verbs, Lith. kláusti ‘to ask questions’, klausýti ‘to listen’, Latv. klàust ‘to ask questions’ and klàusît / klaũsît ‘to listen’ exhibit intriguing morphological and accentological distributions. For a long time, this has interested linguists as shown by numerous previous studies starting with Schulze (1904). Despite several proposals put forward so far, researchers have not yet agreed on a historical interpretation of the acute tone of Lith. kláusti, or on the historical relationship of kláusti to its cognates not only in Balto-Slavic but also in Indo-European languages. In this paper, all the relevant data and hypotheses available to the current author will be examined again, and a more probable historical interpretation will be sought.